2021
DOI: 10.1111/1440-1681.13456
|View full text |Cite
|
Sign up to set email alerts
|

TPPP3 inhibits the proliferation, invasion and migration of endometrial carcinoma targeted with miR‐1827

Abstract: Objective and design Database screening indicated that tubulin polymerization‐promoting protein 3 (TPPP3) was involved in pathogenesis of multiple cancer types. miR‐1827 has a potential role in a variety of human cancers. However, the role of TPPP3 and its underlying molecular mechanism in endometrial cancer (EC) has not been investigated. Herein, we aimed to reveal the role of TPPP3/miR‐1827 in EC progression. Methods Tumour tissue and whole blood samples were collected for the detection of TPPP3 expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Moreover, 35 studies investigated the role of miRNAs in the regulation of tumor growth and EC metastasis in vivo in murine models [ 18 , 19 , 24 , 36 , 41 , 42 , 44 , 45 , 49 , 51 , 52 , 53 , 56 , 62 , 69 , 70 , 72 , 73 , 92 , 93 , 101 , 111 , 117 , 119 , 122 , 126 , 128 , 136 , 137 , 144 , 145 , 151 , 157 , 160 , 166 ]. Eight miRNAs were identified as oncomiRNAs in vivo (miR-106a, miR-107-5p, miR-130b, miR-183, miR-222-3p, miR-494-3p, miR-544a, and miR-652) and 27 as tumor suppressor miRNAs (miR-23a, miR-23b, miR-26a, miR-29a-5p, miR-29b, miR-34a, miR-34b, miR-99a, miR-101, miR-129, miR-142, miR-148b, miR-194, miR-199a/b-5p, miR-200c, miR-204, miR-214-3p, miR-302a-5p, miR-326, miR-361, miR-367-3p, miR-372, miR-449a, miR-490-3p, miR-499a, miR-505, and miR-1827).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 35 studies investigated the role of miRNAs in the regulation of tumor growth and EC metastasis in vivo in murine models [ 18 , 19 , 24 , 36 , 41 , 42 , 44 , 45 , 49 , 51 , 52 , 53 , 56 , 62 , 69 , 70 , 72 , 73 , 92 , 93 , 101 , 111 , 117 , 119 , 122 , 126 , 128 , 136 , 137 , 144 , 145 , 151 , 157 , 160 , 166 ]. Eight miRNAs were identified as oncomiRNAs in vivo (miR-106a, miR-107-5p, miR-130b, miR-183, miR-222-3p, miR-494-3p, miR-544a, and miR-652) and 27 as tumor suppressor miRNAs (miR-23a, miR-23b, miR-26a, miR-29a-5p, miR-29b, miR-34a, miR-34b, miR-99a, miR-101, miR-129, miR-142, miR-148b, miR-194, miR-199a/b-5p, miR-200c, miR-204, miR-214-3p, miR-302a-5p, miR-326, miR-361, miR-367-3p, miR-372, miR-449a, miR-490-3p, miR-499a, miR-505, and miR-1827).…”
Section: Resultsmentioning
confidence: 99%
“…Microtubule is the main component of mitotic spindle, which controls cell division and chromosome segregation (50). Studies have revealed that TPPP3 gene can inhibit cell proliferation, induce apoptosis and cell cycle arrest, and inhibit tumor growth (51)(52)(53). TPPP3 protein is also involved in the development and regeneration of musculoskeletal and nervous system (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…In this, we confirmed that circ_0000808 could act as miR-1827 sponge in NSCLC. MiR-1827 acted as a tumor suppressor to hinder the development of many cancers, including hepatocellular carcinoma [27,28], colorectal cancer [29], and endometrial cancer [30]. In the past research, miR-1827 had been found to inhibit the lung cancer cell growth, metastasis, and angiogenesis [31][32][33].…”
Section: Discussionmentioning
confidence: 99%